Features of consumer behaviour in the sphere of fast food catering on the Moscow market - A. N. Timokhovich; A. A. Bekreneva (Цифровая социология)
The article presents the results of the empirical research of consumer behaviour features in the sphere of fast food catering in the Moscow market. The research method is a questionnaire survey with the use of digital technologies. The article reveals the loyalty of consumers to the visited fast food establishments; their motivation to visit new such places is determined; the awareness of consumers about the opening of new fast food establishments is studied; their preferences regarding the use of meal delivery services of these places and staying at them are revealed. The conclusions are formulated that direct visit to fast food restaurants remains a popular social practice among a significant part of consumers; digital meal delivery services of these places is actively used by consumers; visiting fast food establishments and ordering meal delivery there are typical for representatives of low-, middle-, and high-income audience segments; the communication activity of new fast food restaurants being opened is insufficient; the audience’s expectations from visiting these places and ordering food from them are not limited to the satisfaction of basic needs. The results of the research can be useful for the development of marketing strategies and advertising campaigns in the sphere of fast food catering as well as for the adjustment of business strategies of the restaurants.